Методика и алгоритм построения зон радиодоступности станций радиоконтроля - Коржуков, К. Н. (ХНУРЭ, 2012)
The given work is devoted to methodology building coverage zone of fixed radio monitoring tools. The signal power at the receiver of radio monitoring tool computes in line with radio propagation model recounted in the Recommendation ITU-R P. 1546-2 for UHF Field-Strength Prediction over Fresh-Water Mixed Paths